Phytochemical Profile, Antioxidant, Antimicrobial and Cytoprotective Effects of Cornelian Cherry (Cornus mas L.) Fruit Extracts - Mara Aurori; Mihaela Niculae; Daniela Hanganu; Emoke Pall; Mihai Cenariu; Dan Cristian Vodnar; Andrea Bunea; Nicodim Fiţ; Sanda Andrei (MDPI AG, 2023)
Cornus mas L. is characterized by an increased quantity of bioactive compounds, namely polyphenols, monoterpenes, organic acids, vitamin C and lipophilic compounds such as carotenoids, being anciently used in the treatment of various diseases. This paper's objectives were to characterize the phytochemical profile of Cornus mas L. fruits and to evaluate the in vitro antioxidant, antimicrobial and cytoprotective effects on renal cells exposed to gentamicin. As such, two ethanolic extracts were obtained. The resulting extracts were used to assess the total polyphenols, flavonoids and carotenoids through spectral and chromatographic methods. The antioxidant capacity was assessed using DPPH and FRAP assays. Due to the high content of phenolic compounds analyzed in fruits and the results obtained regarding antioxidant capacity, we decided to further use the ethanolic extract to investigate the in vitro antimicrobial and cytoprotective effects on renal cells stressed with gentamicin. The antimicrobial activity was assessed using agar well diffusion and broth microdilution methods, with great results regarding Pseudomonas aeruginosa. The cytotoxic activity was assessed using MTT and Annexin-V assays. According to the findings, extract-treated cells had a higher cell viability. However, at high concentrations, viability was shown to decline, most likely due to the extract and gentamicin's additive effects.